Analysis of Concrete Pavement Slab resting on Non-uniform Elastic Foundation using the Finite Element Method - An, Le Vinh; Hiep, Nguyen Trong; Tien, Dao Ngoc (Engineering, Technology & Applied Science Research, 2023)
During the rigid pavement design, the concrete slab working on the base/subbase and subgrade is usually modeled as the slab on the elastic foundation. However, the non-uniform distribution of materials in the base or subgrade layers naturally exists in real conditions and should be considered. In this paper, a finite element method for calculating concrete pavement slabs on an elastic foundation with non-uniform stiffness distribution is developed. This study applies 4-node finite elements and Mindlin plate theory to formulate the finite element equations. The results predicted by the proposed approach are verified analytically. Calculation examples are conducted with the practical settings to investigate the influence of slab and foundation stiffness parameters on the slab displacement.